FINANCIAL STABILITY OF RURAL MUNICIPALITIES IN POLAND’S LUBLIN VOIVODESHIP IN 2016-2020 - Agnieszka Gałecka; Marzena Ganc (Polityki Europejskie, Finanse i Marketing)
The stability of public services and the financial situation of local governments has a significant impact on a nation’s economic development. It also affects the long-standing process of political reforms aimed at promoting the efficiency of public sector units, their balanced budgets and financial stability. It is a concept defined in different ways, which is due, among other things, to its multifaceted nature and the lack of precisely defined measures to assess this phenomenon.The main objective of the paper was to assess the financial stability of rural municipalities in Poland’s Lublin voivodeship in 2016-2020. Within the framework of the main objective, ratio analysis and survey research was conducted. The paper was based on the study of literature on the subject, reports on the implementation of budgets in the studied municipalities published by the Regional Chamber of Accounts in Lublin, and a survey questionnaire.Based on the analyses, it was found that the studied municipalities in 2016-2020 recorded sustainability in terms of fiscal policy, and a stable level of financial liquidity and debt, albeit with a relatively low level of revenue independence. The crisis in 2020 caused by the Covid-19 pandemic caused a significant increase in the current expenditures of local government units compared to revenues, which were less than planned, although it did not significantly worsen thefinancial performance of the surveyed municipalities. In the opinion of the respondents (heads of rural municipalities), the vast majority of rural municipalities in the Lublin voivodeship were financially stable and the Covid-19 pandemic generally did not have a significant impact on theirlevels of stability.